2013
DOI: 10.1007/s00192-013-2074-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of pelvic organ prolapse: a historical review with emphasis on the anterior compartment

Abstract: Many surgeons have tried to find the ideal surgical therapy for anterior compartment prolapse, but to date, this has not been achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 41 publications
0
19
0
2
Order By: Relevance
“…Historically the treatment of anterior wall prolapse has been problematic, and as our study illustrates it is similar after both RASC and RSHS. Placing the mesh as distal as possible on the anterior vaginal wall could possibly improve anterior compartment results.…”
Section: Discussionmentioning
confidence: 57%
“…Historically the treatment of anterior wall prolapse has been problematic, and as our study illustrates it is similar after both RASC and RSHS. Placing the mesh as distal as possible on the anterior vaginal wall could possibly improve anterior compartment results.…”
Section: Discussionmentioning
confidence: 57%
“…At present, the “ideal” cystocele correction plan remains undefined. 26 Having objective measures to identify failure sites in each women whose measurements fall outside a normal range could, in the future, help identifying the best surgical plan for the individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…When pharmacologic treatments and mechanical solutions to POP and urinary incontinence fail, surgical approaches to reinforce pelvic floor muscles and prevent recurrent prolapse or incontinence are available. 81,82 Since the 1950s, surgeons have experimented with a variety of synthetic and natural grafts to reinforce the pelvic floor to prevent POP and incontinence. Adaptation of tantalum mesh used for hernia repair for POP was first described in 1955, although persistent defects in the vaginal wall after surgery were common.…”
Section: Transvaginal Meshmentioning
confidence: 99%
“…84 Long-term follow-up of individuals with POP repaired by using high-density, nonabsorable polypropylene or poly-ethylene showed that despite improved sexual function and resolution of prolapse, there remained poor satisfaction (only 42% of individuals reported satisfaction with mesh at 23 months’ postprocedure). 82,85 …”
Section: Transvaginal Meshmentioning
confidence: 99%
See 1 more Smart Citation